Factors and Kinetics of Fat, Oil and Grease Deposit Formation in Kitchen Wastewater - Xin Yan; Dongyang Ren; Jingtao Feng; Zhi Tang; Zheng Fang (Salehan Institute of Higher Education, 2026)
This study systematically investigated key parameters influencing fat, oil, and grease (FOG) deposit formation in kitchen wastewater and elucidated the underlying chemical kinetics. Gas chromatography–mass spectrometry (GC–MS) was employed to characterize the composition of FOG deposits. Single-factor experiments and response surface methodology were used to identify the most significant factors contributing to saponification and determine optimal conditions for FOG accumulation. GC–MS demonstrated lower quantitative error rates than Fourier transform infrared (FTIR) spectroscopy and acid–base titration, with oleic acid identified as the predominant free fatty acid (FFA) component. The optimal saponification conditions were as follows: C₁₈H₃₄O₂:CaCl₂ mass ratio of 1:1.40, pH value of 7, reaction temperature of 30°C, and reaction duration of 1440 min, under which the maximum predicted saponification extent was 77.932%. Additionally, the kinetic model showed that FOG saponification followed a second-order reaction, with an activation energy of 53.1 kJ·mol−1 and a pre-exponential factor of 5.4 × 107 L·mol−1·min−1. Overall, this research enhances the existing theoretical framework of FOG deposit formation by integrating engineering simulation with chemical kinetics and provides quantitative parameters to directly inform pipeline blockage mitigation and wastewater treatment optimization.